ANALISIS FORMAL SENI LUKIS KARYA SOEGENG TOEKIO TAHUN 2000-2015 - Isnanta, Satriana Didiek (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2015)
This article discusses the formal aesthetic work Soegeng Toekio years 2000-2015. It is based on the understanding that the aesthetic value of a work of art can be formed by the work itself, and standard views deserve is requiring the work itself, rather than coming from outside work which is seen as an extra factor aesthetic.The approach used is the aesthetic approach using aesthetic theory by De Witt H. Parker, in his book The Principles of Aesthetics (1920), quoted by The Lian Gie in the book "Philosophy of Beauty" mentions six principles of aesthetics form, namely: 1). The principle of organic unity, 2). The principle of theme, 3). The variation principle according to themes, 4). The principle of balance, 5). The principle of development, and 6). The principle of hierarchy.The works Soegeng Toekio studied from 2000 to 2015 year. The work can be grouped into two major parts, the first is the search for, where Soegeng Toekio started trying to break away from the grip wayang beber and looking for his own visual style (2000-2004) and the second, are the works that have been able to represent Soegeng Toekioâ€™ visual styles (2005-2015).Â Keywords: Soegeng Toekio, painting, formal analysis, aesthetics De Witt H. Parker